Perspectives of medicine, human biology, and nursing undergraduates on transversal skills learning: a mixed-methods study - Nathalia Silva Fontana-Rosa; Luis González-de Paz; Ana C. Codina-Rodríguez; María Pérez-Riart; María del Mar Carrió-Llach (BMC Medical Education)
Abstract Background In health sciences practice, interpersonal skills, critical thinking, and learning-to-learn are crucial transversal skills. Effective teaching necessitates the understanding of undergraduates’ views. This study explored undergraduate experiences in human biology, medicine, and nursing degrees in learning transversal skills. Methods An exploratory sequential mixed method design with qualitative data collection and a subsequent online survey study. Three focus groups were conducted with third- and fourth-year undergraduates, and data were analyzed with thematic analysis. The online survey targeted undergraduate students from all academic years to address inconclusive details. Analysis entailed descriptive statistics, and associations differences in responses by degrees were analyzed using chi-square tests or Fisher’s Exact Test. Results Thirteen undergraduates participated in focus groups and 159 in the online survey. Three thematic areas emerged: the training received and its perceived relevance, the evaluation, and the learning methods. Undergraduates expressed that transversal skills were necessary for self-personal growth and professional development; however 50.7% reported not receiving specific training. Human biology and medicine undergraduates reported less training in critical thinking compared to nursing (29.03% and 32.7% vs. 76%, p < 0.001) and in interpersonal and relational skills (16.1% and 16.3% vs. 57%, p < 0.001). Subjectivity is an issue compared to traditional testing, with 39.6% of undergraduates reporting knowing the assessment methods of transversal skills and 56% trusting the preparation of teaching staff. >80% of undegraduate students wanted more participatory methodologies —from classroom methodology to problem-based assessments and simulation, while plenary lectures and gamification were less preferred. Conclusion Health sciences undergraduates advocated for effectively integrating transversal skills in their programs. Nursing undergraduates showed higher satisfaction and expressed having experienced more transversal skills learning than human biology and medicine undergraduates. Undergraduates required educators to receive more support and training in adopting methodologies that facilitate transversal skill acquisition through changes in the assessment methods and substantive transformation of the program curricula.